Direct writing of stretchable metal flake conductors: improved stretchability and conductivity by combining differently sintered materials. (5th June 2020) - Rahman, Md Saifur; Grau, Gerd
Abstract: Stretchable and flexible electronics with elastic interconnects is critical for electronics to be compatible with wearable applications. Especially fabricating such interconnects with printing technology promises rapid, low-cost, and mass manufacturing. Here, a novel direct-write manufacturing process is presented for a stretchable conductor using an extrusion printer and a micron size silver flake ink as the conductive material without expensive nanomaterials. Conductivity increases as the sintering temperature is increased but at the cost of limited stretchability. To overcome this trade-off, we place one mildly sintered line on top of a fully sintered line to create a hybrid serpentine feature. These two lines of a hybrid feature have two different stretchability-conductivity profiles, synergistically improving both the stretchability and conductivity. With this method, a maximum stretchability of 120% strain is obtained with a minimal change in resistance by a factor of 2.8. This stretchable conductor can endure more than 250 cycles of stretching and releasing under 40% strain. The aggregate electrical conductivity is in the range of 4.74*10 4 S cm −1, which is far superior to any carbon filler based printable composites.